Todurujo na Kadurok (empowering youth): study protocol of an HIV self-testing and edutainment comic cluster randomised trial among refugee youth in a humanitarian setting in Uganda. Issue 11 (23rd November 2022) - Logie, Carmen H; Okumu, Moses; Loutet, Miranda G; Coelho, Madelaine; Berry, Isha; Gittings, Lesley; Odong Lukone, Simon; Kisubi, Nelson; Atama, Malon; Kyambadde, Peter
Abstract : Introduction: Refugees experience HIV vulnerabilities due to the confluence of displacement, violence and poverty. HIV self-testing, understudied with refugees, is a promising method to increase testing uptake, yet challenges remain with linkages to confirmatory testing following a positive HIV self-test. This study aims to evaluate the effectiveness of HIV self-testing kits and 'edutainment' comics in increasing HIV testing and HIV status knowledge among refugee youth aged 16–24 years in Bidi Bidi Refugee Settlement, Uganda. Methods and analysis: This study will be conducted in Bidi Bidi. We conducted a qualitative formative phase with focus groups (n=40) to generate knowledge of barriers and facilitators of HIV prevention, testing and care among refugee youth (aged 16–24) in Bidi Bidi. These findings were used to create comic scenarios aligning with edutainment approaches to health promotion and inform a four-arm cluster randomised controlled trial in Bidi Bidi using a 2×2 factorial design: (1) HIV self-testing alongside edutainment comics, (2) HIV self-testing alone, (3) edutainment comic alone and (4) standard of care. The target sample size will be 120 youth (30 per arm), who will be enrolled in the trial and followed for 3 months. Data will be collected at baseline and 3 months after enrolment. The primary outcomes (HIV testing frequency, HIV status knowledge) and secondary outcomes (linkage to confirmatory HIV testing, HIV care linkage, HIV self-test kit use, HIV-related stigma, HIV knowledge, safer sex efficacy, condom use, adolescent sexual and reproductive health (SRH) stigma, sexual relationship power, access to SRH services) will be evaluated using descriptive statistics and regression analyses. Ethics and dissemination: This study was approved by the University of Toronto Research Ethics Board, Mildmay Uganda Research Ethics Committee and the Uganda National Council for Science and Technology. Results will be shared in peer-reviewed publications and community knowledge sharing. Trial registration number: NCT05213689 .